Factors Affecting Accounting Learning Achievement of Students during the Pandemic - Susanti, Ineke; Suranto, S (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study aims to determine the factors affecting student achievement in accounting learning during the pandemic. The factors tested were teacher teaching methods and student learning independence. This research belongs to a quantitative study with a survey design. The research was conducted at SMK Negeri 1 Juwiring, Central Java Province, Indonesia. The population comprised 70 students, with a sample of 20 students taken by simple random sampling. Data were collected using a questionnaire and documentation. The hypothesis test consisted of a t-test, f-test, multiple regression analysis, relative contribution and effective contribution. The results unveiled that (1) teacher teaching methods partially had a significant effect on accounting learning achievement, with a significance value of 0.004 < 0.05; (2) student learning independence partially had a significant effect on accounting learning achievement, with a significance value of 0.003 < 0.05; (3) teacher teaching methods and student learning independence simultaneously affected student achievement, with a significant value of 0.000 < 0.05. During the Covid-19 pandemic implementing distance learning, teacher teaching methods and student learning independence became crucial factors supporting learning success.